Work, family and public policy changes in latin america: equity, maternalism and co-responsibility - Merike Blofield; Juliana F. Martínez (CEPAL Review, 2014)
Taking account of the substantial increase in female labour market participation that has occurred throughout the Latin American region, this article describes policies adopted with the aim of reconciling work and family responsibilities between 2003 and 2013, and the implications of their design for socioeconomic and gender equity. We look at the cases of Argentina, Brazil, Chile, Costa Rica and Uruguay, five countries which, on the basis of their track records, are the best placed to implement policies to reorganize time, income and services. The empirical analysis indicates, first, that these changes have contributed to socioeconomic equity more consistently than to gender equity. Second, the scale and type of change was found to vary significantly from one country to another. The article concludes by raising a number of substantive questions about the measures, their implementation and effectiveness, and the variations between countries.